Insufficient initial hydration of GCLs from some subgrades: Factors and causes. Issue 6 (December 2018) - Acikel, A.S.; Gates, W.P.; Singh, R.M.; Bouazza, A.; Rowe, R.K.
Abstract: Water retention and hydration tests are reported for three needle punched geosynthetic clay liners (GCLs). GCLs hydration and their maximum hydration capacity were assessed against subgrade soils prepared at different initial gravimetric water contents. The subgrade soil mineralogy and particle size distribution, as well as the carrier geotextiles used in GCLs, are shown to have a significant impact on the GCLs hydration behaviour. This work highlights the need to consider the unsaturated properties of both the GCLs and the subgrade soil when assessing the hydration of the GCLs. At gravimetric water contents above the GCL water entry value (≈30%), some forms of GCL configuration may be better than others with respect to ability to hydrate from a given soil. However, the partial hydration of GCL is mostly controlled by the bentonite microstructure for gravimetric water contents below the water entry value of the GCLs.